Efeitos do modo de exercício no pico do consumo de oxigênio e resposta do lactato sanguíneo em meninos de 11-12 anos - Machado, Fabiana Andrade [UNESP] (2006)
The objective of this study was to analyze the effects of exercise mode (running x cycling) on the indexes related to aerobic fitness (VO2peak and blood lactate response to exercise) in children. Participated of this study 20 active boys apparently healthy (age = 11.48 + 0.41 yr.; body mass = 41.38 + 10.45 kg; stature = 147.45 + 6.56 cm), with sexual maturational level 1 and 2 (pubic hair), which performed two incremental tests, with stages of 3 minutes until voluntary exhaustion, in treadmill (TR) and cycle ergometer (CE), to the determination of peak oxygen uptake (VO2peak) and lactate threshold (LT). The VO2peak was determined through the higher value obtained at intervals of 15 seconds. The LT was determined as the exercise intensity where the first and sustained increase of blood lactate above rest level occurred. The VO2peak (45.16 + 5.98 x 42.93 + 7.51 ml/kg/min), maximal heart rate (196.5 + 6.98 x 187.3 + 9.27 bpm), VO2 at LL (31.82 + 10.09 x 25.19 + 7.36 ml/kg/min) and HR at LL (150.5 + 17.75 x 131.3 + 12.98 bpm) were significantly higher in TR than CE, respectively. Thus, similar to adults, boys of 11 to 12 years present higher aerobic indexes (submaximal and maximal) in running than cycling, which can have important implications for healthy professionals that utilize exercise for the healthy promotion, rehabilitation and experimental designs.